A study on the house preferences among different ethnic groups - Tan, Chin Keng; Ahmad Nor Bakri, Hanani Husna (2013)
The design and use of houses reflect cultural values and ideas, house buyers may have certain housing preferences according to their cultural background. Malaysia is a country of multi ethnic groups. Each of the ethnic groups might have its preferences on houses. It has been observed that there is a gap of understanding on the preferences of different ethnic groups on houses. The objective of this study is to study the house buyers’ preferences on their houses according to ethnic groups. Questionnaire survey has been conducted to achieve the research objective. The areas of preference covered by the questionnaire are land status, direction, location, numbering, security and nearby facilities. A total of one hundred and five (105) questionnaires were distributed. From the total, thirty five (35) were distributed to each race, i.e. Malay, Chinese and India respectively. All questionnaires were personally hand delivered and collected from the respondents by the researcher. A total of 105 answered questionnaires were collected for analysis. The study concludes that there are similarities and differences among different ethnic groups on preferences of houses. The similarities are mainly on the items related to land status, location, security, near to school and supermarket, and easiness of access. Meanwhile, the differences among the ethnic groups observed on the items related to house direction, facing and backing of hills, numbering, near to hospitals, and closed to commercial centre. It is important to understand and respect the differences in preferences among ethnic groups in the choice of their houses as such respect is crucial to maintain a harmony multicultural society.